An Early Experience of “Hanging Maneuver of Liver resection":A Cross-Sectional Study - Khatiwada, Sagar; Belbase, Narayan Prasad; Koirala, Nishnata; Bhujel, Sushim; Shrestha, Nischal; Baral, Suman; Upadhyay, Hari Prasad (Journal of College of Medical Sciences-Nepal, 2023)
Introduction The posterior approach to liver resection is technically difficult, especially when there is a bulky tumor or dense adhesion of right lobe of liver with the risk of tumor dissemination and hepatic vein avulsion. To prevent this, anterior approach of liver resection was used; however, it is technically challenging and can lead to a false line of transection and difficulty in controlling bleeding in deeper parenchymal plane. These technical difficulties are overcome by hanging maneuver liver resection which eases the process of anterior approach. The Objectives of our study were to observe the technical safety, operative duration, operative blood loss, and perioperative complications of hanging maneuver in liver resection. Methods This is a cross-sectional study on the patients who underwent hanging maneuver of liver resection at our center. The perioperative data were analyzed. Descriptive variables were described using frequency and percentage; continuous variables were described using mean and standard deviation. Results A total of 15 patients underwent hanging maneuver of liver resection, majority were male (66.6%) with Child-Pugh score-A of 80%. The most common indication was complex hydatid cyst of liver (33%) and biliocutaneous fistula (13%) that occurred after previous intervention for hydatid cyst of liver (13%). Intraoperative blood loss was 750±343.2 ml and complications grade IIIA were up to 20% as per Clavien Dindo grading system. Conclusions Hanging maneuver of liver resection is a technique that facilitates in elevating liver parenchyma away from IVC and helps in an easier anterior approach. A learning curve and assessment of background liver disease is necessary for its safety.